Approaching apprenticeship systems from a European perspective - Poulsen, Søren Bo [Verfasser]; Eberhardt, Christiane [Verfasser] (Bundesinstitut für Berufsbildung, 2016)
"In view of the high youth unemployment rates in many states of the European Union it is assumed that 'apprenticeship' is a key to providing young people with direct access to the labour market. Furthermore, apprenticeship is viewed as a sustainable model for an education system which takes the needs of the labour market into consideration and uses them for comprehensive competence development based on an occupational standard. This is profitable for the enterprises: Graduates of apprenticeships are broadly qualified and 'vocationally proficient' when they take up their jobs. There are no break-in costs and no need for 'training on the job' by induction at recruitment time. This applies to Germany to the same extent as to Denmark. In many cases the German and Danish VET systems are presented as prototypes of dual apprenticeship systems which are worth copying. This paper addresses policy makers, researchers and practitioners by providing insights in different dual apprenticeship systems and by highlighting alternatives as far as the main features of dual apprenticeship systems are concerned. The paper is aimed to give a general overview of the basic aspects of an apprenticeship system and describes some trends as to the establishment and development of apprenticeship systems. The paper provides a number of examples from EU countries but also makes relevant detours to other countries to illustrate the wide range of apprenticeship systems. Focus is placed on countries where apprenticeship constitutes an important part of the formal VET system." (Authors' abstract, BIBB-Doku)

"Betriebsnahe Ausbildungsmodelle haben seit der Wirtschaftskrise in Europa Konjunktur. Angesichts der hohen Zahlen von Jugendarbeitslosigkeit in vielen Ländern der Europäischen Union wird unterstellt, dass 'apprenticeship' ein Schlüssel dafür ist, den Jugendlichen einen direkten Zugang zum Arbeitsmarkt zu erschließen. In betriebsnahen und dualen Ausbildungsmodellen werden tragfähige Modelle gesehen, wie die Bedarfe des Arbeitsmarktes im Bildungssystem Berücksichtigung finden und in eine umfassende Kompetenzentwicklung auf der Basis eines beruflichen Standards münden. Für die Unternehmen ist dies lukrativ: Absolventinnen und Absolventen sind breit qualifiziert und 'beruflich handlungsfähig', wenn sie ihre Beschäftigung aufnehmen. Einarbeitungskosten und ein Angebot an 'Training on the job' entfallen weitgehend. Vorliegendes Diskussionspapier gibt einen kleinen Überblick über die grundlegenden Prinzipien von betrieblichen Ausbildungsmodellen bis hin zu dualen Systemen und illustriert diese anhand von Beispielen aus europäischen Ländern. Es reflektiert darüber hinaus die Vielfalt beruflicher Ausbildungssysteme außereuropäischer Länder und lädt zur weiteren Diskussion ein." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; I 2.2 Europa; Berufsbildungssystem; Betriebliche Berufsausbildung; Modell; Transfer; Europa